Evaluation of Potential Factors Affecting Knee Function in Athletes Following Anterior Cruciate Ligament Reconstruction - Naderi, Aynollah; Piri, Maryam (Journal of Clinical Physiotherapy Research, 2022)
Introduction: A review of previous studies showed conflicting findings regarding the relationship between athlete-related factors and knee function following ACL reconstruction. Therefore, this study aimed to investigate the relationship between athlete-related factors and knee functional outcomes after ACL reconstruction. Materials and Methods: this study was a cross sectional study which carried out between October 2021 and March 2022 in the city of Sanandaj, Iran. The statistical sample of the study consisted of 43 athletes aged 19–43 years who underwent ACL reconstruction. For assessing Knee function the Osteoarthritis and Knee Injury Outcome Questionnaire (KOOS) was used. Athletes’ characteristics such as weight, height, body mass index, and activity levels (recreational, competitive, and elite) were recorded using a researcher-made demographic questionnaire. The smoking habit, type of graft used, and affected foot were also assessed. Results: Age, body mass index, weight, and gender can predict various ACL reconstruction outcomes (P<0.05). Age predicted 29% of changes in symptoms and knee stiffness predicted 18% of changes in quality of life of athlete. Body mass index predicted 29% of changes in knee pain, 19% of changes in symptoms and knee stiffness, 17% of changes in ADL, 19% of changes in sports activity, and 13% of changes in athletes’ quality of life (P<0.05). Weight only predicted 12% of changes in athletes’ sports activities (P<0.05). Gender was able to predict 15% of changes in activities of daily livings, 13% of sports activity, and 12% of changes in athletes’ quality of life (P<0.05). Conclusion: According to the findings of the present study, there is a relationship between age, weight, body mass index, and sex and knee functions following ACL reconstruction. Due to the limitations of this study, it is better to examine this issue longitudinally in future studies.